Bio-methanol production from oil palm residues: A thermodynamic analysis. (15th December 2020) - Im-orb, Karittha; Phan, Anh N.; Arpornwichanop, Amornchai
Highlights: The bio-methanol production from unutilized oil palm residues is presented. Gasification operating conditions affect bio-methanol production. The once-through process is technically better than the process with PSA offgas recycle. Exergy analysis reveals a high improvement potential for the gasifier. Abstract: The thermodynamic analysis of bio-methanol production from oil palm residues was performed using a process model developed in Aspen Plus. Among the different types of oil palm residues, i.e., trunk, frond, and empty fruit bunch, the trunk residue offers the highest synthesis gas (syngas) (H2 and CO) yields via the gasification process; therefore, it was selected as the biomass model compound. The effect of gasification operating conditions on the syngas composition, yield, bio-methanol production, energy consumption, and exergy performance was examined. The yield of syngas increased with increasing gasifying temperature, whereas that of bio-methanol exhibited the opposite trend due to the decrease in H2 concentration of the syngas. The gasifier was an important unit for enhancing the exergy efficiency of the system, which was decreased when the equivalent ratio (ER) and gasifying temperature increased. Recirculating pressure swing adsorption offgas to the gasifier did not benefit bio-methanol production, nor did it improve energy and exergy performance. The maximum yield of bio-methanol was achieved by a once-through process that maintained the gasifying temperature at 750 °C and ER at 0.25. Under these conditions, the maximum energy and exergy efficiencies were 38.57 and 25.44%, respectively.